Psychological Predictors of Mental Toughness in Elite Tennis: An Exploratory Study in Learned Resourcefulness and Competitive Trait Anxiety. Issue 3 (December 2014) - Cowden, Richard G.; Fuller, Dana K.; Anshel, Mark H.
The purpose of this study was to examine the extent to which two constructs, learned resourcefulness and competitive trait anxiety, measured by the Self-Control Schedule and Sports Competition Anxiety Test, respectively, predicted mental toughness on the Sports Mental Toughness Questionnaire among male and female elite tennis players. The participants included two NCAA Division 1 (U.S.) intercollegiate tennis teams comprising eight male ( M age = 19.4 yr., SD = 1.2) and eight female ( M age = 20.9 yr., SD = 1.4) players and their respective head coaches ( N = 2, M age = 28 yr., SD = 5.7). Results of regression analyses indicated that learned resourcefulness was the primary predictor of athlete self-rated mental toughness and that competitive trait anxiety was relatively unrelated to coach and athlete-rated mental toughness. The positive significant relationship between mental toughness and learned resourcefulness suggests that the latter may be an integral component of mental toughness, at least among elite tennis players. Further research is needed to examine related components of mental toughness, including learned resourcefulness, and to determine the effectiveness of interventions that increase mental toughness to optimal levels, particularly as a function of sport type.